2019
DOI: 10.1177/2054358119882658
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Accelerometer-Based Physical Activity and Sedentary Time Among Kidney Transplant Recipients

Abstract: Background:Physical activity is recommended for kidney transplant recipents as it may improve outcomes including mortality, exercise capacity, muscle strength, and health-related quality of life.Objective:The objective of this study was to examine accelerometer-based physical activity and sedentary time profiles among kidney transplant recipients and examine possible demographic and clinical correlates of physical activity and sedentary time.Design:Cross-sectional.Setting:Edmonton, Alberta, Canada.Patients:Kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…These measures of PA were also associated with PCS and four subscales of the SF-8, but not with the MCS of the SF-8.In the present study, the number of steps taken, but not the amount of moderate-to-vigorous PA performed, correlated with hypertension and obesity. Our findings are consistent with those of two other studies of transplant recipients12,13 that showed associations between objectively measured PA level and BMI. Internationally, a moderate-to-vigorous PA level of ≥ 150 min/week is considered to be effective in the prevention of metabolic syndrome and its components,26 but three-quarters of our participants failed to achieve this level.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…These measures of PA were also associated with PCS and four subscales of the SF-8, but not with the MCS of the SF-8.In the present study, the number of steps taken, but not the amount of moderate-to-vigorous PA performed, correlated with hypertension and obesity. Our findings are consistent with those of two other studies of transplant recipients12,13 that showed associations between objectively measured PA level and BMI. Internationally, a moderate-to-vigorous PA level of ≥ 150 min/week is considered to be effective in the prevention of metabolic syndrome and its components,26 but three-quarters of our participants failed to achieve this level.…”
supporting
confidence: 93%
“…11 Four other studies used accelerometers to measure PA and to evaluate the relationship between PA level and BMI or metabolic abnormalities in patients following transplantation. 12,13 A study of lung transplant patients revealed that obese/overweight patients took a significantly lower number of steps per day than normal-weight controls, but the dietary intake of the two groups did not differ significantly. 12 A study of renal transplant patients aimed to determine the predictors of four PA indicators and found that high BMI was inversely associated with light PA and was positively associated with sedentary time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The criteria for kidney transplant eligibility were strict in 1987 compared to contemporary criteria. Second, the patients in the previous studies were more specifically selected, whereas the patients in our study were recruited consecutively representing a real-world cohort of patients known to lead a sedentary life style [16]. Third, the dialysis vintage in the transplant recipients of our study was substantial (mean >2.5 years), possibly contributing to the poor MEC at the follow-up ergometry test.…”
Section: Discussionmentioning
confidence: 99%